Volcanoes - Geological and Geophysical Setting, Theoretical Aspects and Numerical Modeling, Applications to Industry and Their 2018
DOI: 10.5772/intechopen.77970
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic Scoria as Cement Replacement

Abstract: Numerous volcanic scoria (VS) cones are found in many places of the world. Many of them have not yet been investigated, although few have been used as binders for a very long time. The use of natural pozzolans as cement replacement could be considered as a common practice in the construction industry due to the related economic, ecologic and performance benefits. This chapter highlights the advantages and disadvantages of the use of volcanic scoria as cement replacement in concrete mixes in terms of fresh and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…Volcanic scoria cones exist in large numbers around the world, such as in Syria, Turkey, Iran and others [1][2][3][4][5][6][7][8][9][10]. One may find more details on the use of VS as a substitute for Portland cement, in the chapter recently published by the author [11].…”
Section: Introductionmentioning
confidence: 99%
“…Volcanic scoria cones exist in large numbers around the world, such as in Syria, Turkey, Iran and others [1][2][3][4][5][6][7][8][9][10]. One may find more details on the use of VS as a substitute for Portland cement, in the chapter recently published by the author [11].…”
Section: Introductionmentioning
confidence: 99%
“…The use of marble powder is more effective as a substitute for sand which is revealed by [28]. The presence of scoria improves the strength of concrete by creating condensed C-S-H gel with the presence of CaO and SiO 2, whereas marble powder is microfine filler, by filler effect it improves the compressive strength of scoria according to those [24,27,28] researchers, which is done on marble waste and scoria individually as cement and sand replacement. Since CaO and SiO 2 are major cement making oxides different studies shows that, replacing marble waste and scoria individually as cement improve the compressive strength due to the presence of those cement making oxides produce additional C-S-H gel but in this study since marble waste and scoria used as a sand and the methodology of using marble and scoria as sand and cement is different so, it requires more advanced microstructure investigation to determine the extent of the effect of marble waste and scoria on compressive strength.…”
Section: Chemical Characterization Of Marble Waste and Scoriamentioning
confidence: 93%
“…The chemical and Mineralogical composition of volcanic scoria varies widely and depends on its source. Owing to their formation process scoria, volcanic scoria consists of crystalline and non-crystalline particles as glassy particles [24]. Scoria ejected during basaltic eruptions vary considerably in its vesicularity, but densities are much greater than those pumice materials.…”
Section: Scoriamentioning
confidence: 99%
See 1 more Smart Citation
“…); (ii) others derived from rocks and earths [7]. An overview on the use of volcanic scoria as cement replacement can be found in the paper recently published by the author [8]. Although there are numerous works on using natural pozzolan as a substitute for cement, few studies investigating on volcanic scoria have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%